2019
DOI: 10.18502/kls.v4i13.5306
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Exclusive Breastfeeding (ASI) and Mother Heightwith Incident Rates Stunting among Child Age 2-5 Years In Barombong Public Health Center, Gowa, Sulawesi Selatan

Abstract: Background:The incidence of stunting is one of the nutritional problems experienced by toddlers in the world today. Indonesia ranks fifth for stunting in the world, which is around 37% (nearly 9 million) children. Toddlers with stunting will have a level of intelligence that is not optimal, making children more vulnerable to disease and in the future can be at risk of decreasing levels of productivity. In the working area of the Barombong Public Health Center, it was reported that nutrition issues, especially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…Studies showed strong association between exclusive breastfeeding and reduction of the risk of stunting. 16 Exclusive breastfeeding has many benefits, one of which is for the growth and development of babies, especially height. Breast milk contains calcium that can be absorbed better than calcium in formula milk, so that body growth can be optimized and the possibility of stunting can be prevented.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed strong association between exclusive breastfeeding and reduction of the risk of stunting. 16 Exclusive breastfeeding has many benefits, one of which is for the growth and development of babies, especially height. Breast milk contains calcium that can be absorbed better than calcium in formula milk, so that body growth can be optimized and the possibility of stunting can be prevented.…”
Section: Discussionmentioning
confidence: 99%
“…Mikawati's research (2019) stated that there was a significant relationship between maternal height and the incidence of stunting in children with p value = 0.026 (Mikawati et al, 2019), as well as from another study by Nasution et al (2014) that maternal height is significantly associated with stunting in children OR 2,14 (95% CI 1,08-4,33). Mothers with less than normal height are at risk of 2 times greater risk of having stunting children (Nasution et al, 2014).…”
Section: Maternal Height and Its Relationship To Stuntingmentioning
confidence: 96%
“…The incidence of stunting in children is caused by various factors, including household and family factors, inadequate complementary feeding and breastfeeding that is not exclusive (Hidayat et al, 2022). Mikawati (2019) reported that there was a relationship between exclusive breastfeeding and the incidence of stunting (p value = 0.015) (Mikawati et al, 2019).…”
Section: Exclusive Breastfeeding and Its Relationship To Stuntingmentioning
confidence: 99%
“…Ditambah lagi, berat badan Ibu juga mempunyai pengaruh dalam kejadian stunting pada anak. (Mikawati et al, 2019) Hasil wawancara dengan salah satu kader posyandu, bahwa saat ini salah satu hal yang menjadi perhatian Puskesmas adalah bagaimana meningkatkan kesadaran Ibu hamil terkait status gizi selama hamil dengan mengkonsumsi pangan yang tersedia di sekitar lingkungan masyarakat, salah satunya adalah daun kelor. Pemanfaat daun kelor sendiri oleh masyarakat sejauh ini hanya diolah sebagai sayur berkuah, tentunya jika dikonsumsi terus menerus dengan olahan yang tidak variatif akan menimbulkan rasa bosan dan akhirnya berhenti untuk mengkonsumsi.…”
Section: Pendahuluanunclassified